What is an ecologically or biologically significant area? - D. C. Dunn; J. Cleary; S. DeLand; N. Bax; L. K. Bentley; C. Curtice; B. Donnelly; P. K. Dunstan; C. Barrio Froján; K. M. Gjerde; V. Gunn; D. E. Johnson; et al. (npj Ocean Sustainability)
Abstract The first iteration of the ecologically or biologically significant areas (EBSA) process, which aims to ascribe ecological value to marine and coastal regions, has drawn to a close. This Convention on Biological Diversity process has collated vast amounts of information to describe 338 EBSAs that span from estuaries to ocean trenches. To increase the utility and accessibility of the ocean of knowledge generated by the EBSA process, and to support appropriate application of the dataset, clarity is required around the types of areas described, the biodiversity they hold, and the rationale for their selection. In this study, we provide a holistic answer to the question: What is an EBSA? We identify geographic and taxonomic gaps in EBSA descriptions, trends in the levels of protection observed, and ways forward to improve the uptake and appropriate use of the outputs of this singular intergovernmental process.